TINJAUAN TENTANG KUALITAS PELAYANAN RUMAH SAKIT AJI MUHAMMAD PARIKESIT DI KOTA TENGGARONG - Sanora, Faisal Erlangga (PREDIKSI, 2013)
Overview of the Quality of Service at the Hospital Aji Muhammad Parikesit in town Tenggarong, Background in writing of the author made in the field of service providers, the hospital should be able to provide the best possible service in order to satisfy the patient. In writing this paper the auther formulates the research problem as follows : How efforts to improve the quality of care in hospitals in the city Aji Muhammad Parikesit Tenggarong?. The aim in this paper is to determine the service quality improvement efforts in hospitals Aji Muhammad Parikesit in Town Tenggarong. The focus of research in this thesis is to increase the quality of services that include tangibles, reliability, responsiveness, assurance and emphaty. Types of research used in this paper is the kind of research is descriptive